Burnout in Medical and Psychiatric Nurses/Role of Physical Activity as a Prevention Method in a Small-Scale Study - Chaziris Georgios (2013)
Abstract, Introduction, Literature Review, Burnout a a Phenomenon and Related Conseqwuences, Maslow's Hierarchy of Need and Concepts Related to Practitioners and Organizations Health, Medical and Psychiatric Setting, Physical Activity and Stress and Burnout, Research Aims and Sope, Methodology, Design, Participants, Materials, Procedure, Analytic Strategy, Results, Discussion, Main Findings, Implications of the Findings, Strengths and Limitations, Further Research, Conclusion, References, Appendices, Application Letter.